EFEKTIVITAS SENYAWA KURKUMIN DALAM EKSTRAK RIMPANG KUNYIT (C. DOMESTICA) SEBAGAI ANTIINFLAMASI PADA OSTEOARTRITIS LUTUT PRIMER: SYSTEMATIC REVIEW - Renasya Nur Sarifah (2021)
According to the American College of Rheumatology (ACR), Osteoarthritis is a condition of cartilage degradation, remodelling bone, osteophyte formation, and synovial inflammation. The high incidence of osteoarthritis in the elderly requires effective management to reduce the decline in quality of life. Turmeric (Curcuma domestica) is one of the traditional plants widely used by the people of Indonesia in various kinds of treatment. Several studies have shown the effectiveness of curcumin compounds in turmeric rhizome extract (Curcuma domestica) as an anti-inflammatory against primary knee osteoarthritis. This study aims to determine the effectiveness of curcumin compounds in rhizome extracts turmeric (Curcuma domestica) as an anti-inflammatory in primary knee OA in the future as an alternative treatment therapy. In this study, a systematic review was used using a literature search related to Curcuma domestica as an anti-inflammatory in primary knee osteoarthritis through database searches from Pubmed and Google Scholar. The literature search was carried out using the 2015 PRISMA-P method, and journal elimination was carried out using the JBI Critical Appraisal Checklist. The results obtained are nine journals that explain the effectiveness of curcumin compounds in rhizome extract Curcuma domestica as an anti-inflammatory against primary knee osteoarthritis. Based on the results of the data synthesis, it can be concluded that the curcumin compound in rhizome extract Curcuma domestica has effectiveness in reducing inflammation in primary knee osteoarthritis.